Meningkatkan Hasil Belajar Rekorder dengan Metode Tutor Sebaya di Kelas VIII.1.SMPN.1 Patamuan Kabupaten Padang Pariaman - Arisma Arisma; Syeilendra Syeilendra; Tulus Handra Kadir (SENDRATASIK UNP, 2014)
Abstract This research was aimed at describing the implementation of Peer-Tutor method in Recorder class at SMPN I Patamuan. This was a qualitative research. The data of the research was collected through observation, interview and library study. The result of the research showed that the use of Peer-Tutor method in Ambilkan Bulan Bu song could improve the students’ learning achievement. This could be seen from the students’ average score which was above the Minimum Standart Score (75) indicating that the learning outcome was 100% achieved. Key word: Recorder clas, Peer-Tutor.